Health, Disability and Mortality Differences at Older Ages between the US and England1. (September 2016) - Banks, James; Keynes, Soumaya; Smith, James P.
Abstract: This paper examines health status differences between England and the United States, with an emphasis on the implications of any health disparities for health care cost differences between the two countries. We first document health status differences in disease prevalence, disability, mortality and co‐morbidity. We find higher disease prevalence in the US than in England (confirming previous findings) but much smaller differences between the two countries in disability and mortality. We attribute the smaller differences in disability to the fact that disability measures rely primarily on subjective questions on experiencing disabilities, which are reported differently in the two countries. Smaller mortality differences are most likely due to a combination of earlier disease diagnosis and more effective disease treatment in the US. Co‐morbidity is a common and important dimension of disease in both countries that is often neglected in scientific papers, especially by economists. We find, however, that disease prevalence has little implication for out‐of‐pocket health care costs in the US except for relatively few individuals with particular diseases. Instead, costs are more associated with incidence than prevalence and with those who are going to die in the next year or two. Co‐morbidity is associated with higher costs but even this association is limited to a relatively small fraction of people who are co‐morbid.